Implementasi Akad-Akad Ekonomi Syariah Pada Dhuafa Mart Dalam Mendukung Perkembangan Ekonomi Syari’ah - Zakir, Muhammad; Khairi, Rifqil; Hasda, Mifta; Maini, Nur (Journal of Community Sustainability, 2024)
This study aims to analyze the implementation of sharia economic contracts at Dhuafa Mart in supporting the development of sharia economy and empowerment of the dhuafa community. The study uses a qualitative method with a case study approach, through in-depth interviews, observation, and documentation as data collection techniques. The results of the study indicate that Dhuafa Mart implements several sharia contracts, such as murabahah (buying and selling with a profit margin), ijarah (renting), and qardhul hasan (goodwill loans). The implementation of these contracts has been proven to provide economic and social benefits, including transparency in transactions, easy access for the dhuafa community, and real contributions to sharia-based economic empowerment. These findings indicate that a business model such as Dhuafa Mart can be a strategic instrument to expand sharia financial inclusion and strengthen the socio-economic impact of Islam in society